Les gestes dans l’activité en situation de travail - Jacques Leplat (Perspectives Interdisciplinaires sur le Travail et la Santé)
A gesture is a polysemic notion, as is testified by the considerable bibliography devoted to it. The present paper is limited to the study of gestures that comprise the work activity. Our study attempted to determine which themes in particular have captured the attention of ergonomists and work psychologists, the objective being to show the place that should be reserved for gestures in the analysis of work activities. Two functionalities, expressive and instrumental, are considered here, in particular the different forms they take and roles they play in developing and managing activities. Other functionalities are also briefly discussed with regard to future research avenues. The conclusion emphasizes the interest of relating the study of gestures to that of the activity that comprises them, each one shedding light on the other.